2021
DOI: 10.1108/ijaim-02-2021-0052
|View full text |Cite
|
Sign up to set email alerts
|

The impact of financial instruments disclosures on the cost of equity capital

Abstract: Purpose This study aims to investigate the impact of financial instrument disclosures under the International Financial Reporting Standard (IFRS) 7 on the cost of equity capital (COEC). Design/methodology/approach The sample consists of 56 banks listed in the Gulf cooperation council (GCC) stock markets over 7 years from 2011 to 2017. A self-constructed index is used to measure the compliance level in addition to quantitative methods and panel data regression adopted to test the research hypotheses. Findin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 96 publications
0
8
0
Order By: Relevance
“…Some studies navigate the impact of adopting a single financial instrument standard on the firm value, value relevance or the cost of equity capital. For example, Yamani et al (2021) studied the impact of financial instrument disclosures on the cost of equity capital, and they revealed that compliance with IFRS 7 disclosures reduces the cost of equity capital. On the other hand, Gómez-Ortega et al ( 2022) studied the impact of the first application of IFRS 9 on the financial statements of the credit institutions listed in Spain and found positive and negative impacts of the first adoption of IFRS 9 on the results of the companies.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Some studies navigate the impact of adopting a single financial instrument standard on the firm value, value relevance or the cost of equity capital. For example, Yamani et al (2021) studied the impact of financial instrument disclosures on the cost of equity capital, and they revealed that compliance with IFRS 7 disclosures reduces the cost of equity capital. On the other hand, Gómez-Ortega et al ( 2022) studied the impact of the first application of IFRS 9 on the financial statements of the credit institutions listed in Spain and found positive and negative impacts of the first adoption of IFRS 9 on the results of the companies.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This transparency helps investors gain confidence in the financial institution's operations and reduces the estimated risk associated with investing in it. This implies that they would find contentment with a reduced proportion of returns in exchange for the assurance they receive (Yamani et al, 2021b). Therefore, compliance with IFRS 7 disclosure requirements leads to a lower cost of capital.…”
Section: Regressions' Results and Discussionmentioning
confidence: 99%
“…This reform has consequently amended the dispositions of IFRS 7 regarding the classification of financial instruments, credit impairment and hedge accounting. These recent updates of IFRS 7 have stimulated an interest in financial instrument disclosure among academics and practitioners (Yamani, 2021b). Hence, it seems interesting to investigate the economic consequence of compliance with a standard in perpetual change like IFRS 7.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other limitation of our study is that we have focused only on the financial institutions, which future studies could examine such relationship on the non-financial institutions. Recent studies show that the adoption of mandatory IFRS affects cost of capital in GCC [48], it would be interested to examine the impact of SDGs reporting on cost of capital in the same context. Finally, research shows that COVID-19 pandemic affects the quality of external auditors [49]additional research is needed to explore the impact of the quality of external auditors on SGDs reporting in times of COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 99%